If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -2(x + 5) = 9 Reorder the terms: 4 + -2(5 + x) = 9 4 + (5 * -2 + x * -2) = 9 4 + (-10 + -2x) = 9 Combine like terms: 4 + -10 = -6 -6 + -2x = 9 Solving -6 + -2x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -2x = 9 + 6 Combine like terms: -6 + 6 = 0 0 + -2x = 9 + 6 -2x = 9 + 6 Combine like terms: 9 + 6 = 15 -2x = 15 Divide each side by '-2'. x = -7.5 Simplifying x = -7.5
| F=1.8(30)+32 | | 3x-6x^2=0 | | 7-x-6x=-28 | | 160=-8(1-3p) | | 7(m-1)-6(m+5)=-37 | | (2x+3y-4z)-(x-y-z)= | | 6y+14=15-9y+14 | | 3(x-7)=8 | | -x-29=-13+2x | | x-9+x=3 | | -x-29=-12x-1 | | 4x^3+20x+10=0 | | y^2-14y=-36 | | 42x+50=1500 | | 2x^2+10x=-15 | | -10=4(x-5)+6x | | 2y+2(y-2)=7y-5(y-10) | | 2x^2+10x=15 | | 70=6x+5x-7 | | 4(-5-5x)=-200 | | 40+273= | | (2y+5)(3y+7)= | | 2(-5+x)=14 | | -8(x+1)+5(3x-4)=6(x-6)+14 | | 10ac*6ab*(-2bc)= | | 6(8+x)=6 | | 2x^2+3x=4 | | 14x+32=70 | | 6x-6-3x=-18 | | 6(-11+2n)-2n=-7(-n+3) | | 2(6+7x)=68 | | 0.75a+14=8 |